Growing Pomegranates in Florida: Establishment Costs and Production Practices - Feng Wu; Zhengfei Guan; Gary E. Vallad (EDIS)
The study described in this 6-page fact sheet written by Feng Wu, Zhengfei Guan, and Gary Vallad and published by the UF/IFAS Food and Resource Economics Department provides a description of pomegranate production practices and preliminary cost estimates to inform investment and production decisions when growers look to diversify and grow pomegranate as a niche crop. http://edis.ifas.ufl.edu/fe1024